MUATAN INFORMASI TAMBAHAN ARUS KAS DARI AKTIVITAS OPERASI, INVESTASI DAN PENDANAAN - DILAH UTAMI CAHYANI (Jurnal Bisnis dan Akuntansi, 1999)
The major purpose of a statement of cashflows is to provide information about the cash receipts and cash payments of an entity for a period of time. Cash flow information should help investors and creditors assess an entity's ability to generate positive future net cash flows and to meet its current and long-term obligations, including positive future dividend payment. In addition, the statement of cash flows should help users assess the reasons for the differences between net income and the related cash receipts and payment. Finally, the statement of cash flows should help users to determine the effects of both cash and non-cash investing and financing transactions on an entity's financial position. To achieve these objectives, a statement of cash flows should report the cash effects of an entity's operations, its investing transaction and its finansial transaction. This study investigate the relationship between the important in statement of cash from financing and accruals and return securities in Jakarta stock exchange. The result of this study show that all off test value are not significant. In the other means, this study can't find the relationship between the important information in statement of cash flows and return securities.